2020
DOI: 10.4067/s0717-92002020000300353
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of sampling intensity in forest inventories to estimate the total height of eucalyptus trees

Abstract: Reduction of sampling intensity in forest inventories to estimate the total height of eucalyptus treesReducción de la intensidad de muestreo en inventarios forestales para estimar la altura total de eucaliptos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other studies showed similar results, training ANN to estimate the height of Eucalyptus trees. To reduce sampling intensity, ANN trained with quantitative and qualitative variables and a clone in their input layers showed the best performance, meeting the objective of the study [89]. Furthermore, research has used ANN to predict the commercial volume of Eucalyptus clones by assessing region, farm (for each region) and clone group, increasing the accuracy of the predictions in the study [90].…”
Section: Discussionmentioning
confidence: 81%
“…Other studies showed similar results, training ANN to estimate the height of Eucalyptus trees. To reduce sampling intensity, ANN trained with quantitative and qualitative variables and a clone in their input layers showed the best performance, meeting the objective of the study [89]. Furthermore, research has used ANN to predict the commercial volume of Eucalyptus clones by assessing region, farm (for each region) and clone group, increasing the accuracy of the predictions in the study [90].…”
Section: Discussionmentioning
confidence: 81%
“…Os procedimentos de mensuração florestal são elementos fundamentais e merecem atenção, por serem a base para a determinação do volume de madeira em uma determinada área (Gregoire et al, 2016). A informação do volume em um povoamento florestal é imprescindível para o manejo de florestas, levando em conta que grande parte dos processos produtivos em uma empresa é dependente dos dados de produtividade que são obtidos por meio do inventário (Dantas et al, 2020a;Terra et al, 2022). O volume para árvore individual serve como ponto de partida para decisões relacionadas a tratos silviculturais, colheita e transporte da produção volumétrica da madeira.…”
Section: Introductionunclassified
“…These units are layered and connected to each other by weights that store experimental knowledge and weight the inputs of each unit. Thus, the acquired knowledge becomes available for use (Braga et al 2007, Dantas et al 2020a.…”
Section: Introductionmentioning
confidence: 99%